Prokaryotic ubiquitin-like protein remains intrinsically disordered when covalently attached to proteasomal target proteins. (January 2018) - Barandun, Jonas; Damberger, Fred; Delley, Cyrille; Laederach, Juerg; Allain, Frédéric; Weber-Ban, Eilika
Abstract Background The post-translational modification pathway referred to as pupylation marks proteins for proteasomal degradation inMycobacterium tuberculosis and other actinobacteria by covalently attaching the small protein Pup (prokaryotic ubiquitin-like protein) to target lysine residues. In contrast to the functionally analogous eukaryotic ubiquitin, Pup is intrinsically disordered in its free form. Its unfolded state allows Pup to adopt different structures upon interaction with different binding partners like the Pup ligase PafA and the proteasomal ATPase Mpa. While the disordered behavior of free Pup has been well characterized, it remained unknown whether Pup adopts a distinct structure when attached to a substrate. Results Using a combination of NMR experiments and biochemical analysis we demonstrate that Pup remains unstructured when ligated to two well-established pupylation substrates targeted for proteasomal degradation inMycobacterium tuberculosis, malonyl transacylase (FabD) and ketopantoyl hydroxylmethyltransferase (PanB). Isotopically labeled Pup was linked to FabD and PanB by in vitro pupylation to generate homogeneously pupylated substrates suitable for NMR analysis. The single target lysine of PanB was identified by a combination of mass spectroscopy and mutational analysis. Chemical shift comparison between Pup in its free form and ligated to substrate reveals intrinsic disorder of Pup in the conjugate. Conclusion When linked to the proteasomal substrates FabD and PanB, Pup is unstructured and retains the ability to interact with its different binding partners. This suggests that it is not the conformation of Pup attached to these two substrates which determines their delivery to the proteasome, but the availability of the degradation complex and the depupylase.